Penerapan Pembatasan User Wi-Fi Pada Kantor Yayasan Patra Mandiri 01 Palembang - Rahmat Novrianda Dasmen; Muhamad Dito Nugraha; Adelia Adelia (J-ICON : Jurnal Komputer dan Informatika, 2022)
The need for the use of the internet has become very important in helping daily life along with the development of information technology. Wi-fi (wireless fidelity) has a role in building computer network systems today. Wi-Fi can be defined as a technology that uses electronic equipment to exchange data using radio waves (wireless) through a computer network. Yayasan Patra Mandiri 01 Palembang office has used the Wi-Fi facility but there is no user restriction facility available. This causes frequent lag when accessing the internet. This study aims to limit Wi-Fi users at the Yayasan Patra Mandiri 01 Palembang office and to find out the importance of using a Wi-Fi network in meeting information needs at the Kantor Yayasan Patra Mandiri 01 Palembang office. The user restriction process is carried out by configuring internet protocol (IP) addresses using the dynamic host configuration protocol (DHCP) facility on Mikrotik equipment. The result of this research is that there is a user restriction facility on the Wi-Fi network of the Patra Mandiri 01 Palembang Foundation Office.